Description of a new species of Saliocleta Walker, 1862 (Lepidoptera, Notodontidae, Spatalinae, Ceirini) and description of S. notia Schintlmeister, 1997 female from Thailand - Pellinen, Markku J. (Zootaxa, 2017)
One new Saliocleta (type-species nonagrioides Walker, 1862), S. puyak sp. n., and the female of S. notia Schintlmeister, 1997 are described from Northern Thailand. The male genitalia structure of Saliocleta is examined in detail.